1985
DOI: 10.1080/03015521.1985.10426099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-harvest treatment and mower and header types on seed loss and hard seed content at mowing, recovery, and separation when harvesting a white clover seed crop

Abstract: To cite this article: P. T. P. Clifford & S. J. M. McCartin (1985) Effects of pre-harvest treatment and mower and header types on seed loss and hard seed content at mowing, recovery, and separation when harvesting a white clover seed crop, New Zealand Journal of Experimental Agriculture, 13:4, 307-316, DOI: 10.1080/03015521.1985 Abstract A preliminary on-farm survey of white clover (Trifolium repens L.) crop seed losses at pickup for threshing and separation indicated that operator skills and/or machinery we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…comm. ), and suggest that perhaps the very high harvesting losses which commonly occur (Clifford & McCartin 1985) could possibly be reduced if harvesting occurred closer to 30 days after peak flowering. This requires further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…comm. ), and suggest that perhaps the very high harvesting losses which commonly occur (Clifford & McCartin 1985) could possibly be reduced if harvesting occurred closer to 30 days after peak flowering. This requires further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Forage legumes have not been fully domesticated yet and often show pod dispersal and/or dehiscence of pod prior to harvest. For example, seed shattering coupled with dehiscence of pod is high in Lotus corniculatus L., while pod dispersion is high in annual medics, Trifolium incarnatum L. and T. repens , where losses up to 40% of the total seed yield are reported ( Clifford and McCartin, 1985 ).…”
Section: Developing Strategies For Seed Production and Seed Producersmentioning
confidence: 99%
“…The need for a five-year break requirement relates to the timespan required for decay/elimination of seed contributed from the previous cultivar harvest losses, to a level where purity of the change cultivar is not compromised. Initial research (Clifford et al 1990) has shown a timespan of five years was needed to meet first generation quadrat requirements for all harvest loss calculations; based on the range of seed losses reported by Clifford and McCartin (1985) (Table 4). Even then, inter-row spraying was essential to meet the mandatory requirement of no more than one per quadrat for the four higher loss treatments.…”
Section: Five Year Paddock History and Buried Seed Countsmentioning
confidence: 99%
“…Standard procedures are not being adhered to, therefore results are highly variable and do not allow any finite determination of success level. Secondly, the fixed sampling procedure takes no account of paddock area (1 to 50 ha) let alone distance between header offal trails (up to two-fold difference); these being the zones of higher seed load deposition (Clifford & McCartin 1985). As a consequence, extremes of 100-fold in magnitude can never be consistently measured because of sampling error.…”
Section: Five Year Paddock History and Buried Seed Countsmentioning
confidence: 99%